The diversity of private slaving strategies in classical Athens - Porter, Jason D. (2019)
To a degree, classical Athenian slavery is very easy to describe. It was a system that attached rights of ownership to particular individuals within Athens’ polity, legally defined as a distinct status group: douloi. Nevertheless, the legal definition of slavery does not in and of itself account for some of the different characteristics of slavery as it appears in different examples throughout classical Athenian history. In order to provide a more nuanced picture of slavery and its consequences, this PhD discusses Athenian slavery from the perspective of slaveholding strategies: the varying ways in which classical Athenian slave-owners employed slaves and the different methods of coercion they applied as appropriate to these varying uses. This approach is drawn from the work of Joseph Miller, who tried to eschew definitions of ‘the institution of slavery’, in favour of a more dynamic progression of varied, though interrelated, historical phenomena. In so doing, this thesis sheds light on both the complexity of Athens’ slave system and its equally complex interaction with Athens’ society and economy. It also helps describe the wide and often commented on variation in the lives of Athenian slaves.